2011
DOI: 10.1016/j.jpowsour.2011.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Application of a detailed dimensional solid oxide fuel cell model in integrated gasification fuel cell system design and analysis

Abstract: a b s t r a c tIntegrated gasification fuel cell (IGFC) systems that combine coal gasification and solid oxide fuel cells (SOFC) are promising for highly efficient and environmentally sensitive utilization of coal for power production. Most IGFC system analysis efforts performed to-date have employed non-dimensional SOFC models, which predict SOFC performance based upon global mass and energy balances that do not resolve important intrinsic constraints of SOFC operation, such as the limits of internal temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Example cycle conceptualization and detailed thermodynamic analyses applied to coal-fi red FC/GT systems has been accomplished by Li et al . ( 2010Li et al . ( , 2011aLi et al .…”
Section: © Woodhead Publishing Limited 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Example cycle conceptualization and detailed thermodynamic analyses applied to coal-fi red FC/GT systems has been accomplished by Li et al . ( 2010Li et al . ( , 2011aLi et al .…”
Section: © Woodhead Publishing Limited 2012mentioning
confidence: 99%
“…( , 2011aLi et al . ( , 2011b and Li ( 2010 ). Table 9.2 presents representative results from detailed cycle conceptualization and thermodynamic analyses after Li ( 2010 ).…”
Section: © Woodhead Publishing Limited 2012mentioning
confidence: 99%
“…This specific operating condition may require dedicated flow field configurations and distribution patterns in order for the cell voltage to comply with the lower local Nernst potential induced by the intense reactant consumption, as discussed in literature for the case of coal based cycles [43]. Therefore a sensitivity analysis on the air utilisation factor has been carried out in order to evaluate its effects on the overall plant performance.…”
Section: Air Utilisation Factor Sensitivitymentioning
confidence: 99%
“…They have presented cycles such as fuel cell (FC) topping, fuel cell bottoming, direct and indirect cycles. A detailed two dimensional planar SOFC system integrated with a gasification unit was studied and it was shown that the detailed model allows prediction of temperature changes at various points across the SOFC [34]. This allows for the safe operation of the hybrid system.…”
Section: Fuel Cells and Gas Turbinesmentioning
confidence: 99%